Multi-disciplinary teaching implementations: methods, challenges, and future considerations as described by Finnish primary school teachers - Raynor-Karjalainen, Ramona (My University, 2025)
The need for 21st Century Skills has acted as a catalyst for widespread curricula changes featuring multi-disciplinary modules. In this research, aspects of multi-disciplinary implementation including the methods, challenges, and benefits as described by Finnish primary school teachers are explored. The purpose of this study is to understand how teachers perceive these curriculum changes and if they meet expected goals so that multi-disciplinary teacher training and future implementation in the classroom can be developed. Nine Finnish primary school teachers who had participated in multi-disciplinary modules in teacher training schools, Finnish primary schools, and international schools participated in this qualitative, phenomenological study. Teachers participated in semi-structured interviews with open-ended questions presented in either English or Finnish based upon participant preference. The study presents a snapshot of multi-disciplinary themes and practices in selected Finnish schools. Successful multi-disciplinary modules are multi-faceted and, while teachers have embraced their new roles, some uncertainty remains. There could be more supporting structures, training, and materials to facilitate more consistent outcomes and streamline multi-disciplinary implementation processes. The study also found that assessment was challenging and underutilized, students were rarely involved in meaningful planning, and additional student support may be needed to ensure more consistent outcomes.
Keywords: Multi-disciplinary implementation, multi-disciplinary teaching, multi-disciplinary assessment, multi-discipinary themes and practices, Finland.